WALKING AS A MEANS OF INFLUENCING FITNESS, WELL-BEING AND MENTAL WELL-BEING - Vaclav Bunc (Matej Bel University, 2022)
The current lifestyle is characterize by an ever-increasing deficit of physical activity, which results in a reduction in the fitness of the population and a demonstration of health complications that are associated with reduced fitness. One of the most effective and safest physical activities is walking, which, with sufficient load intensity, significantly reduces the physical deficit, but also has a number of health benefits and significantly affects the preconditions for physical activity. In addition to physical fitness and health, walking also affects an individual's psyche, depression, aggression and anxiety. In the communication, we present an overview of the formative and preventive effects of walking as well as the principles of designing a walking-based exercise program.